التفسير العلمي للقرآن: ضوابط لغوية وإشكالات دلالية: Scientific Interpretation of the Quran: Linguistic Constraints and Semantic Issues - Dr. Hafiz Haris Saleem; Dr. Hafiz Moazzum Shah (Al Manhal Research Journal, 2024)
This Subject of Scientific Interpretation of the Holy Quran is a very significant topic for the young generation & contemporary world. The Quran severally challenges mankind that it is not composed of any human, but it is the very words of Almighty, the Glorified and Exalted. It was revealed to the Prophet PBUH and transmitted to us through an authentic and continuous narration without doubt. This Subject of Scientific Interpretation of the Holy Quran is a very significant topic for the young generation & contemporary world. Moreover, this is a remarkable way to show the miracle of the Holy Quran in this world by discussing the Scientific Phenomenon and accuracy of its verses. Therefore, it is recognized the need to establish rules for interpreting the Quran to preserve its meaning and protect it from being misinterpreted, particularly in scientific interpretation of the Holy Quran. This article tried to set these linguistic rules for the interpretation of the Holy Quran. The method used for this research was descriptive and applied.